ANALISIS PERENCANAAN SUMBER DAYA MANUSIA PADA KANTOR POS KOTA GUNUNGSITOLI - Tio Putri Marlina Lase; Palindungan Lahagu; Fatolosa Hulu; Idarni Harefa (Lembaga Pengembangan Kinerja Dosen, 2025)
In the era of globalization and digitalization, organizations are required to have an effective human resource management (HR) strategy to face the challenges of increasingly fierce competition. This research aims to analyze HR planning at the Gunungsitoli City Post Office in order to improve the quality and effectiveness of public services. With a qualitative descriptive approach, data is collected through observation, interviews and documentation. The research results show that the Gunungsitoli City Post Office is facing a mismatch between workforce needs and the availability of competent employees, especially in dealing with developments in digital services and customer demands. Human resource planning that is not yet optimal has an impact on service quality and operational efficiency. Therefore, strategic and comprehensive HR planning is needed to support the long-term success of the organization.